Growth and yield performance of Pegaga (Centella asiatica) to different types of organic fertilizer and levels of planting media / Nur Masriyah Hamzah - Hamzah, Nur Masriyah (2013)
The demand for herbal medicines has increased tremendously in recent years. Many Malaysian plants which have been traditionally used to treat certain ailments are now being processed using modern technology for the production of functional foods and tonics including Centella asiatica (pegaga). Recently, the adverse effect of modern agriculture causes several problems in environment and one of the solutions is by turning to organic agriculture. The objective of this study was to determine the best combination of three different types of organic fertilizer (chicken manure (FI), goat manure (F2), and vermicompost (F3) and four different levels of planting media (clay soil-control (M1), clay soil + rice husk ash (M2), clay soil + sawdust (M3), and clay soil + rice husk ash + sawdust (M4)) to the growth and yield performance of pegaga. This experiment was conducted on clay soil under open rainshelter structure at Makmal Luaran Program Teknologi dan Pengurusan Perladangan, (AS220), Universiti Teknologi MARA Shah Alam. A Randomized Complete Block Design (RCBD) with twelve (12) treatments and three (3) replications has been employed in this study. The first data collection was conducted on the 12th January 2009 and was continued to collect data at weekly basis until 60 days. Then the data was analyzed by using the Microsoft Excel and Minitab software. At the end of this experiment, the result showed that the best combination treatment was obtained when plants grown with chicken manure combine with clay soil and rice husk ash (FIM2) pegaga.